Improving Student Learning Outcomes of Class V Elementary School 13 Koto Besar on Photosynthetic Material in Green Plants Through Example Non Examples Learning Models. : Meningkatkan Hasil Belajar Siswa Kelas V SD Negeri 13 Koto Besar pada Materi Fotosintesis pada Tumbuhan Hijau Melalui Model Pembelajaran Example Non Examples. - Siti Mutmainah (Journal of Vocational Education and Information Technology (JVEIT), 2022)
Science subjects are one of the exact subjects in Elementary School (SD), due to the low understanding of students towards science lessons, especially photosynthesis material in green plants in class V SD Negeri 13 Koto Besar, the authors make improvements to learning. The research activity was carried out at SD Negeri 13 Koto Besar in semester 1 of the 2021/2022 school year in 5th grade students, totaling 30 students, consisting of 10 boys and 20 girls.  After teaching and learning activities are carried out using the Example Non Examples learning model, student learning outcomes have increased. This is shown from the data obtained in the pre-cycle learning activities only 11 students who completed the 30 students or 36, 67% who reached the KKM standard. In cycle 1 there was an increase of 17 students who completed from 30 students or 56.67% who achieved the KKM standard, and cycle 2 increased to 23 students who completed or 76.67% who reached the KKM standard, and cycle 3 increased again to 28 students completed or 93.33% who reach the KKM standard. Then the description of the data obtained can be concluded that the use of the Example Non Examples learning model can improve student learning outcomes on photosynthesis material in green plants in class V SD Negeri 13 Koto Besar. Thus, the Example Non Examples learning model is one of the effective learning models in improving student learning outcomes on photosynthesis in green plants.